Politik Hukum memaknai Pemilihan Kepala Daerah dipilih secara Demokratis: Politik Hukum Memaknai Pemilihan Kepala Daerah Dipilih Secara Demokratis - Lubis, Rahmad; Yunus, Nur Rohim; Herlina, Ratna; Shapiulayyevna, Aliyeva Patimat (Yapilin Press, 2025)
The election of regional heads (Pilkada) in Indonesia, which is regulated in Article 18 Paragraph (4) of the 1945 Constitution, has important implications in realizing the principles of democracy and regional autonomy. This article emphasizes that regional heads are elected directly by the people. This study aims to analyze the legal politics contained in Article 18 Paragraph (4) of the 1945 Constitution related to the election of democratic regional heads. Using a normative analysis approach, this study explores the relationship between the principles of democracy, decentralization, and the implementation of regional autonomy in the context of the Regional Elections. The results of the study show that although Article 18 Paragraph (4) provides a constitutional basis for direct regional elections, it also does not rule out the possibility that the election of regional heads through the Regional Representative Council (DPRD) both at the provincial and city district levels, its implementation still faces challenges in terms of the quality of democracy, local political influence, and imbalance between the central and regional governments. The study also identifies the importance of reforms to realize effective decentralization and better quality democracy at the regional level.